The Essential UPP Phosphatase Pair BcrC and UppP Connects Cell Wall Homeostasis during Growth and Sporulation with Cell Envelope Stress Response in Bacillus subtilis - Radeck, Jara; Lautenschläger, Nina; Mascher, Thorsten (Frontiers in Microbiology, 2017)
The bacterial cell wall separates the cell from its surrounding and protects it from environmental stressors. Its integrity is maintained by a highly regulated process of cell wall biosynthesis. The membrane-located lipid II cycle provides cell wall building blocks that are assembled inside the cytoplasm to the outside for incorporation. Its carrier molecule, undecaprenyl-phosphate (UP), is then recycled by dephosphorylation from undecaprenyl-pyrophosphate (UPP). In Bacillus subtilis, this indispensable reaction is catalyzed by the UPP-phosphatases BcrC and UppP. Here, we study the physiological function of both phosphatases with respect to morphology, cell wall homeostasis and the resulting cell envelope stress response (CESR). We demonstrate that uppP and bcrC represent a synthetic lethal gene pair, which encodes an essential physiological function. Accordingly, cell growth and morphology were severely impaired during exponential growth if the overall UPP-phosphatase level was limiting. UppP, but not BcrC, was crucial for normal sporulation. Expression of bcrC, but not uppP, was upregulated in the presence of cell envelope stress conditions caused by bacitracin if UPP-phosphatase levels were limited. This homeostatic feedback renders BcrC more important during growth than UppP, particularly in defense against cell envelope stress.